Rhetoric of Hope: Ecological Restoration for a Troubled Planet - Zytkoskee, Adrian Matthew; Sayed , Sana; McCarthy, Phillip (Journal of Ecohumanism, 2024)
When exposed to environmental rhetoric, it is easy to feel hopeless. With experts regularly claiming that our CO2 levels have crossed the 'point of no return,' it is no surprise that traditional and multimodal texts choose to focus on issues such as the destruction of wilderness, overpopulation, loss of biodiversity, invasive species, pollution, drought, hunger, and ‘no-longer-natural’ disasters. Such information, perhaps understandably, stymies the catalyst for change and leads many to feelings of impotency and despair. In this article, however, we argue that fear-based rhetoric is a flawed model in environmental communication. Instead, we introduce the field of ecological restoration and illustrate its principles and practices through related, narrative-based literature. Accordingly, we show that ecological restoration, concentrating on real solutions at the local level, presents a message of both environmental and cultural hope. By focusing on positive, actionable steps, we demonstrate that ecological restoration encourages public involvement and promotes a sense of empowerment. This approach shifts the narrative from despair to hope, demonstrating that collective action can make a significant difference. We conclude by arguing that ecological restoration's rhetoric is effective in addressing current environmental degradation, denial, and despair, providing a hopeful and actionable path forward.